Effects of Sourdough on FODMAPs in Bread and Potential Outcomes on Irritable Bowel Syndrome Patients and Healthy Subjects - Menezes, Leidiane A. A.; Minervini, Fabio; Filannino, Pasquale; Sardaro, Maria L. S.; Gatti, Monica; Lindner, Juliano De Dea (Frontiers in Microbiology, 2018)
Background Fermentable, Oligosaccharides, Disaccharides, Monosaccharides And Polyols (FODMAPs) are an heterogeneous group of compounds that can be poorly digested and may have a range of effects on gastrointestinal processes. FODMAPs are found in a wide variety of foods, including bread. FODMAPs’ intake is associated with the onset of symptoms of Irritable Bowel Syndrome (IBS). On the other hand, some FODMAPs contribute to the healthy maintenance of intestinal microbiota. Volume increase of bread dough commonly relies on the use of two biological leavening agents, sourdough and baker’s yeast and, in some cases, a combination of both. Scope and Approach The main objective of this review is to discuss the association between FODMAPs and IBS, beneficial effects of FODMAPs on healthy subjects and potential impact of biological leavening agents on FODMAPs content of bread. Key Findings and Conclusions Given that yeasts and lactic acid bacteria, the dominant microorganisms in sourdough, may degrade FODMAPs, it would be possible to modulate the FODMAPs concentration in bread, thus positively affecting consumers’ health.